HASIL BELAJAR PRODUK KREATIF DAN KEWIRAUSAHAAN TERHADAP MINAT BERBISNIS ONLINE HASIL BELAJAR PRODUK KREATIF DAN KEWIRAUSAHAAN TERHADAP MINAT BERBISNIS ONLINE USAHAAN TERHADAP MINAT BERBISNIS ONLINE SISWA TATA BOGA SMK NEGERI 3 KLATEN: HASIL BELAJAR PRODUK KREATIF DAN KEWIRAUSAHAAN TERHADAP MINAT BERBISNIS ONLINE - Pratiwi, Enggar (Universitas Sarjanawiyata Tamansiswa, 2024)
This study aims to find out; 1) the learning outcomes of creative and entrepreneurial products, 2) the interest in doing business online, and 3) the influence of creative and entrepreneurial product learning outcomes on the interest in doing business online of culinary students of SMK Negeri 3 Klaten. This study hypothesizes that there is an influence of creative and entrepreneurial product learning outcomes on online business interest in grade XI students in the field of culinary expertise at SMK Negeri 3 Klaten for the 2022/2023 academic year. This type of research is descriptive quantitative. The results showed that 1) The learning outcomes of creative and entrepreneurial products in the category are very high with a relative frequency of 100%. 2) The interest in doing business online for students in the category is very low with a relative frequency of 32.9%. 3) There is no significant influence between the learning outcomes of creative products and entrepreneurship on the interest in doing business online, this is indicated by the value of sig (2-tailed) of 0.531 > 0.05, so that interest in doing business online may be influenced by factors not addressed in this study. keywords: learning outcomes, interests, doing business online.